First record of the parasitoid Melittobia hawaiiensis (Hymenoptera: Eulophidae) associated with Emphorini bees (Hymenoptera: Apidae) - Aquino, Daniel Alejandro (2015)
Melittobia hawaiiensis Perkins (Hymenoptera: Eulophidae), a common gregarious ectoparasitoid of aculeate Hymenoptera and other orders of insects, is reported for the first time as a parasitoid of Melitoma segmentaria(Fabricius) (Hymenoptera: Apidae) in Buenos Aires, Argentina